Bisphosphonates and risk of cancers: a systematic review and meta-analysis - Li, Yuan-Yuan; Gao, Li-Jie; Zhang, Yu-Xue; Liu, Shu-Juan; Cheng, Shuo; Liu, Yu-Peng; Jia, Cun-Xian (British journal of cancer, 2020)
Background It is unclear whether bisphosphonates are associated with risk of cancers. Therefore, this meta-analysis aimed to evaluate the effect of bisphosphonates on overall cancers. Methods A search in Pubmed, Embase, Cochrane Library and Web of Science databases was conducted, from the inception date of each resource to September 26, 2019. The summarised effect estimates with 95% CIs were calculated using a random-effect model. Heterogeneity and publication bias were explored. Results Thirty-four articles were included in this study (4,508,261 participants; 403,196 cases). The results revealed that bisphosphonates significantly decreased the risk of colorectal cancer (RR = 0.89, 95% CI: 0.81–0.98), breast cancer (RR = 0.87, 95% CI: 0.82–0.93) and endometrial cancer (RR = 0.75, 95% CI: 0.61–0.94), but no significant association was observed in all-cause cancer. Furthermore, nitrogen-containing bisphosphonates only had protective effects both on breast cancer (RR = 0.94, 95% CI: 0.90–0.99) and endometrial cancer (RR = 0.70, 95% CI: 0.54–0.92). Non-nitrogen-containing bisphosphonates tended to increase the risk of liver cancer (RR = 2.14, 95% CI: 1.23–3.72) and pancreas cancer (RR = 1.75, 95% CI: 1.32–2.33). Conclusion Bisphosphonates are significantly associated with risk reduction of colorectal, breast and endometrial cancer, especially nitrogen-containing bisphosphonates. It should be noted that non-nitrogen-containing bisphosphonates might increase the risk of liver and pancreas cancer. Large prospective cohort studies are needed to find the causal association between bisphosphonates and risk of cancers.